THE VULNERABLE IN TIMES OF PANDEMIC - AN ANALYSIS FROM THE SUBALTERN WORKERS AND THE ELDERLY - Mendes, Lidiana de Pinho; Ferreira de Oliveira, Fernando Henrique [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2020)
This article brings together two researchers who undertake investigations in different geographical contexts and with different actors, but who approach them by paying attention to their social vulnerability. The first is dedicated to the study of the daily work of sweepers of Presidente Prudente/SP, the second focuses on the study of the aging process, the senses and meanings, from the lenses of the geographies of aging. The Covid-19 health crisis in Brazil has demonstrated and accentuated socio-spatial inequalities and deepened social vulnerability. We are committed to presenting reflections based on the social experience of the (the) women(s) and the elderlys, in order to demonstrate the details that corroborate for the complex plot of social determination of the vulnerable. With this, we aim to contribute to the construction of a socially just and attentive reflection to invisible aspects.
Keywords: Covid-19; social vulnerability; street sweepers; elderly